2007
DOI: 10.1080/07434610600924515
|View full text |Cite
|
Sign up to set email alerts
|

Brevity and speed of message delivery trade-offs in augmentative and alternative communication

Abstract: This study is the third in a series of studies that have concentrated on utterance-based systems--which allow the relatively quick selection of full sentences--and investigated trade-offs faced by users of such systems when there is a pragmatic mismatch between the prestored sentence and the current discourse context. While the previous studies focused on trade-offs between speed of message delivery and either relevance or informativeness, this study investigated the effects of trade-offs between speed of mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
11
2
Order By: Relevance
“…These researchers found that a message containing a floorholder with just enough information, no matter how quickly or slowly it was delivered, was preferred over a quickly delivered message with inadequate information. The third study of this series seemed to reverse the previous findings, as McCoy, Bedrosian, Hoag, and Johnson (2007) found that time was of the essence, in that quickly delivered messages with repetitions were preferred over slowly delivered messages without repetitions, regardless of the use of a floorholder message.…”
Section: Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…These researchers found that a message containing a floorholder with just enough information, no matter how quickly or slowly it was delivered, was preferred over a quickly delivered message with inadequate information. The third study of this series seemed to reverse the previous findings, as McCoy, Bedrosian, Hoag, and Johnson (2007) found that time was of the essence, in that quickly delivered messages with repetitions were preferred over slowly delivered messages without repetitions, regardless of the use of a floorholder message.…”
Section: Introductioncontrasting
confidence: 48%
“…Based on lessons learned from face-to-face exchanges regarding both the importance of the timing and strategic use of a floor holder message (Bedrosian et al, 2003;Hoag et al, 2004;McCoy et al, 2007), and considering the meager signaldependent and absent signal-independent information available during telephone calls, it was hypothesized that using a floorholder message would be important to successful communication on the telephone; that perhaps partners would be forgiving of the delays and rate differences inherent when communicating with a person who uses an SGD if a floorholder message explained the situation at the start of the call.…”
Section: Introductionmentioning
confidence: 99%
“…In each experiment, 96 salesclerks viewed scripted, videotaped message error situations in the context of a bookstore interaction; they also completed a questionnaire designed to assess their attitudes toward customers who used AAC. The results showed that situations involving slowly delivered relevant messages were rated more positively than situations in which the messages were quickly delivered but only partly relevant (Bedrosian et al, 2003); situations involving slowly delivered messages with adequate information were rated more positively than quickly delivered messages with inadequate information (Hoag et al, 2004); and situations involving quickly delivered messages with repetition were rated more positively than the slowly delivered, non-repetitive messages (McCoy et al, 2007). The researchers also examined the hierarchy across these three conversational rule violations when latency remained consistently short (Hoag et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…A small number of studies have investigated the infl uence of the types of errors in messages on partners ' attitudes toward those who use AAC. For example, Bedrosian et al tested the effects of AAC messages containing errors on the attitudes of salesclerks toward adults using AAC (Bedrosian et al, 2003;Hoag et al, 2004;McCoy et al, 2007). In each experiment, 96 salesclerks viewed scripted, videotaped message error situations in the context of a bookstore interaction; they also completed a questionnaire designed to assess their attitudes toward customers who used AAC.…”
Section: Introductionmentioning
confidence: 97%
“…Response time is important in conversation as is the avoidance of violations of conversational maxims such as lacking relevance, giving too much or too little information, or delaying response (Bedrosian et al, 2002(Bedrosian et al, , 2003Hoag et al, 2004Hoag et al, , 2008McCoy et al, 2007McCoy et al, , 2010aMcCoy et al, , 2010b. Experiments have been performed on conversational trade-off choices when an utterance-based system is used in goal-directed public situations.…”
Section: Violation Of Conversational Maximsmentioning
confidence: 99%